MENENTUKAN DETERMINAN FLEKSIBILITAS PASOKAN DAN PENGARUHNYA TERHADAP KINERJA PASOKAN: (Sebuah Pendekatan Konseptual) - Ganika, Gerry (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2020)
In a variety of operations management literature, supply flexibility is interpreted as the company's response to supply uncertainty. Although its not a new issue, supply flexibility is still a strategic aspect on operations management, especially in dealing with supply uncertainty in the era of the digital industry (industry 4.0) with its various disruptive effects. The purpose of this study was to reveal the various determinants which strengthen the supply flexibility and its influence on the performance of the supply chain.